2011
DOI: 10.1002/bse.734
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Reduction of Greenhouse Gas Emissions Enhance Firm Value? The Case of Japanese Manufacturing Firms

Abstract: This paper examines the influence of firms' reductions of greenhouse gas (GHG) emissions on firm value, measured by Tobin's q. If the stockholders/investors regard the reduction of GHG emissions as a form of intangible value, the reduction of GHG emissions will enhance firm value. To prove this relation more precisely, this paper analyzes not only the effect of the reduction of GHG emissions on firm value but also that of the market discipline imposed by the stockholders/investors in terms of the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 72 publications
7
113
1
Order By: Relevance
“…The empirical results (H1) confirmed that a reduction in CO 2 emissions did not negatively affect the sustainable development of firms; these results were consistent with the findings reported in previous studies (Brzobohatý & Janský, 2010;Nishitani & Kokubu, 2012;Sariannidis et al, 2013). The empirical results (H1) confirmed that a reduction in CO 2 emissions did not negatively affect the sustainable development of firms; these results were consistent with the findings reported in previous studies (Brzobohatý & Janský, 2010;Nishitani & Kokubu, 2012;Sariannidis et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The empirical results (H1) confirmed that a reduction in CO 2 emissions did not negatively affect the sustainable development of firms; these results were consistent with the findings reported in previous studies (Brzobohatý & Janský, 2010;Nishitani & Kokubu, 2012;Sariannidis et al, 2013). The empirical results (H1) confirmed that a reduction in CO 2 emissions did not negatively affect the sustainable development of firms; these results were consistent with the findings reported in previous studies (Brzobohatý & Janský, 2010;Nishitani & Kokubu, 2012;Sariannidis et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The carbon reduction variables employed by the present study were different from those employed by previous research, such as data obtained from computational formulae (see, e.g., Nishitani & Kokubu, 2012) and data pertaining to macroeconomics released by the various countries (Melike & Tahsin, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The objective of this study is to examine the impacts of carbon emissions and environmental R&D investment on the financial performance of the Japanese manufacturing firms. Japan has been one of the largest manufacturing producers, while at the same time, being one of world's largest carbon emitters (Nishitani and Kokubu, 2012). The mandatory GHGs accounting and reporting system of the Ministry of the Environment was introduced in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Many environmental studies have analyzed the benefits carbon information disclosure brought to enterprise value creation (Chapple, Clarkson & Gold, 2013;Griffin, Lont & Sun, 2011;Nishitani & Kokubu, 2012;Saka & Oshika, 2014). However, these researches might have some limitations.…”
Section: Introductionmentioning
confidence: 99%